Lipoblastoma of the lip - Jochima Cota; Richa R. Borkar; Jitisha J. Savalkar; Paul Chalakkal; Anita Spadigam (Indian Journal of Pathology and Microbiology)
Lipoblastomas are benign tumors arising from embryonic white fatty cells that continue to proliferate and develop during the postnatal period. It commonly affects children 3 years of age or younger, with the neck being the most frequent site in the head and neck region. Only 10% of cases are seen at 10 years or above. The etiopathogenesis of lipoblastomas is linked to polysomy and rearrangement of chromosome 8q11–13 with or without the involvement of the pleomorphic adenoma gene 1 (PLAG1) gene. Here, we report one of the first cases of lipoblastoma of lip in a 10-year-old boy with atypical immunohistochemical features and the need for thorough clinical and histopathological evaluation of cases with atypical findings. The novel pathogenetic mechanism of lipoblastoma from the cluster of differentiation 34-positive (CD34+) stem cells has also been discussed.